2018
DOI: 10.1038/s41598-018-28669-3
|View full text |Cite
|
Sign up to set email alerts
|

Integer-dimensional fractals of nonlinear dynamics, control mechanisms, and physical implications

Abstract: Fractal dimensionality is accepted as a measure of complexity for systems that cannot be described by integer dimensions. However, fractal control mechanisms, physical implications, and relations to nonlinear dynamics have not yet been fully clarified. Herein we explore these issues in a spacetime using a nonlinear integrated model derived by applying Newton’s second law into self-regulating systems. We discover that (i) a stochastic stable fixed point exhibits self-similarity and long-term memory, while a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…(ii) HR fluctuation depended on two factors: cardiac disturbances and responses, but not a single factor such as cardiac autonomic modulation. It has been demonstrated that wave slope and amplitude depend on the relative strength of external disturbances to internal responses respectively 36 . Based on the wave indicators, HR slope indicator equaled the ratio of the mean of myocardial disturbances to the myocardial electrical resistance coefficient; HR amplitude indicator equaled the ratio of the standard deviation of myocardial disturbances to the relative strength of PNS against SNS activity (PNS-SNS activity).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(ii) HR fluctuation depended on two factors: cardiac disturbances and responses, but not a single factor such as cardiac autonomic modulation. It has been demonstrated that wave slope and amplitude depend on the relative strength of external disturbances to internal responses respectively 36 . Based on the wave indicators, HR slope indicator equaled the ratio of the mean of myocardial disturbances to the myocardial electrical resistance coefficient; HR amplitude indicator equaled the ratio of the standard deviation of myocardial disturbances to the relative strength of PNS against SNS activity (PNS-SNS activity).…”
Section: Discussionmentioning
confidence: 99%
“…denotes the integer part of T∕m) 36 . Consider the observation scales ranging from 1 to 10 seconds and from 1 to 10 minutes and real f1y02, f1o04, chf01, s20641, and 0030.vf1 (which were regarded as the representative heart rate time series of the YOUNG, ELDER, CHF, ST, and VT/VF groups, respectively) on the first scale m = 1.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The most common one is the fractal dimension. Fractal dimensionality is considered a measure of complexity for systems that do not present integer dimensions [25]. However, there are different fractals that have the same fractal dimension.…”
Section: Experimental Characterization Of Fractal Structuresmentioning
confidence: 99%